A study on the behaviour of RC beam with spliced helical end rebar - Saraswathi, Adla; Rao, C.B.K.; Seshu, D. Rama (Journal of Structural Engineering, 2024)
It is known that the reinforcement used in RC beams shall have the proper development length or anchorage lengthto develop its full strength and avoid premature failure. The usual practice to fulfil the code specified developmentlength criteria includes extending the reinforcing bar beyond the theoretical cut-off point, using couplers, headedbars, bars with hooked ends, etc. This paper presents a new method of providing development/anchorage length usingreinforcement with helical ends. The experimental investigation carried out in three phases to study the behaviour ofRC beams provided with continuous / spliced reinforcing bars with helical ends indicated that the behaviour of RCbeam with Helical end Rebar (HeR) is similar to the behaviour of conventional RC beam.